Effect of Practical Training of Tube-shift Technique to Dental Students On Localizing the Anatomic Structures of the Jaws - Azam Ahmadian Yazdi; Samareh Mortazavi; Arash Shaebani (Mashhad University of Medical Sciences, 2018)
Introduction: Awareness of the localization techniques using conventional radiography is essential for all dentists. Although these techniques are theoretically taught to dental students, practical training is needed to enable them to use these modalities in localizing the anatomic structures. The aim of this study was to evaluate the ability of students and the effect of practical learning using educational model on applying vertical and horizontal tube-shift technique. Materials and Methods: This study was conducted among 41 students of the second year of dentistry. They were assigned into two groups of "only theoretical training" and "practical traing with educational model". All the students were tested 2 weeks and 6 months after teaching without previous notification. The scores were evaluated and compared by t-student , Mann-Whitney U and Wilcoxon tests. Results: There was no significant difference between the groups in the pre-test (P=0.171). Nevertheless, in the post-test, the students who were practically educated had a better performance than those with theoretical education (P=0.011). Moreover, no significant difference was observed between males and females considering the mean scores. Conclusion: The practically educated group had a deeper understanding of the subject in comparison to those who were educated theoretically.